Risk Factors And Clinical Outcomes Of Epistaxis In Elderly Patients - Hasnain, Fahad; Ali, Farman; Hafeez, Muhammad; Samiullah, Samiullah; Din Shinwari, Wajih Ud; Ahmad, Siyyar (Journal of Neonatal Surgery, 2025)
Background:Epistaxis is a frequent otolaryngological emergency in elderly patients and is often complicated by multiple comorbid conditions and polypharmacy. Age-related vascular fragility, mucosal atrophy, and widespread use of antithrombotic drugs contribute to increased bleeding severity, higher recurrence rates, and greater need for hospitalization in this population. Objectives:To identify major clinical and medication-related risk factors for epistaxis in elderly patients and to evaluate short-term outcomes including recurrence, transfusion requirement, length of hospital stay, and in-hospital mortality. Methodology:This cross-sectional study was conducted in the Department of ENT of Pak International Medical College, Peshawar from January to June 2025. Eighty consecutive patients aged ≥60 years presenting with active epistaxis were enrolled. Data regarding demographic profile, comorbidities, blood pressure, laboratory parameters, and use of antiplatelet or anticoagulant medications were recorded. Management strategies and outcomes including nasal packing, blood transfusion, hospital stay, and recurrence within 30 days were analyzed using SPSS version 24.0. Associations were tested using chi-square and independent t-tests, with p<0.05 considered significant. Results:The mean age of patients was 68.7 ± 6.4 years; 57.5% were males. Hypertension was present in 65.0% and 51.3% were using antithrombotic drugs. Posterior epistaxis occurred in 36.3% cases and was significantly associated with hospital admission. Patients on antithrombotic therapy had higher transfusion rates than non-users (26.8% vs 8.1%, p=0.018). Poorly controlled hypertension was linked to recurrent bleeding (p=0.031). Mean hospital stay was 3.4 ± 1.9 days and was longer in posterior bleeds with multiple comorbidities (p=0.022). No mortality was recorded. Conclusion:Epistaxis in elderly patients is strongly associated with hypertension, antithrombotic use, and systemic comorbidities, leading to increased recurrence and resource utilization. Early identification of high-risk patients and optimal control of modifiable factors may improve outcomes..